Grafena Oksida dalam Konstruksi: Tinjauan Komprehensif tentang Prospek, Tantangan, dan Perkuatan Semen Berkelanjutan - Ciawi, Yenni; Supariarta, Made Adi; Hidayati, Anissa Maria; Tonyes, Silvia Gabrina (MEDIA KOMUNIKASI TEKNIK SIPIL, 2023)
The growing demand for cement production to support the rapid growth of the construction industry has resulted in a significant contribution to global carbon emissions due to the high energy requirements of cement production. Addressing this issue requires the development of eco-friendly cement modifiers/additives. Graphene, known for its exceptional properties, has emerged as a versatile material in various domains, including construction. Its incorporation into cement has exhibited promising prospects, surpassing geopolymer performance and enhancing cement quality. Nevertheless, challenges persist, such as inadequate dispersion in concrete mixtures and quality control issues during large-scale production. Harnessing the potential of graphene oxide can revolutionize cement performance and contribute to a more sustainable construction industry. Addressing dispersion challenges and ensuring successful large-scale production are pivotal steps towards realizing these benefits. This comprehensive review investigates the potential of graphene oxide in the construction sector, specifically focusing on its capacity to reinforce cementitious composites and highlighting the associated implementation challenges, paving the way for more sustainable cement production with a touch of scientific excellence.